ÀS MARGENS DA DECISÃO: A JUSTIÇA COMO PARIDADE PARTICIPATIVA APLICADA ÀS INDENIZAÇÕES PARA A CONSTRUÇÃO DE EMPREENDIMENTOS HIDRELÉTRICOS - Przybyzeski, Silvana (2017)
Government actions implemented and designed in the last decades to leverage the country's economic growth mainly involve infrastructure works, such as hydroelectric projects. However, the political and institutional context of the current energy policy, essentially focused on the logic of the market, can trigger social impacts to the community affected by the work, especially regarding the participation of the population affected in the decision-making process in regards to the legal compensation. In view of this, the present research has the objective of investigating the effectiveness of social justice in the decision process for indemnification of those affected by the construction of a hydroelectric project in the State of Paraná, based on the assumptions of the theory of recognition proposed by Nancy Fraser. For this, a qualitative field study was carried out using bibliographical sources, documentaries and semi-structured interviews with those affected, which were analyzed based on the assumptions of Critical Discourse Analysis (ACD). Based on the analysis of the research, it can be observed that the Brazilian legal system provides some instruments of popular participation in the processes of evaluation and implementation of hydroelectric projects. However, the procedures are limited in scope, mainly because of the influence of economic power rooted in the political-economic structure of the society and due to the existence of institutionalized standards that, symbolically, place those affected in a lower position than the project executors. Such factors may have been the cause of the denial, for the affected ones, on the condition of parties in social interaction, resulting in a failed recognition in the terms of the theory studied.